Salinity on artificial reproduction of silver catfish (Rhamdia quelen) - Martins,Gabriel Bernardes (2015)
Attempting to improve reproduction performance and ichthyo prophylaxis, this study evaluated the effects of maintaining silver catfish (Rhamdia quelen) broodstock in different saline concentrations (0, 2, 4, 6 and 8‰) on gametes quality and reproductive viability. The results showed that sperm percent motility did not change between 0 and 4‰, but it was reduced at 6‰, and sperm became immotile at 8‰ salinity. Sperm motility time was increased (almost five fold) at 6‰. Salinities up to 4‰ prevented fertilization and hatching, proving their deleterious effects on oocytes and embryos. Therefore, media up to 4‰ salinity may be an alternative for icthyo prophylaxis, although fertilization and incubation must be done in freshwater medium